2020
DOI: 10.1021/acs.joc.0c02137
|View full text |Cite
|
Sign up to set email alerts
|

Melicopteline A–E, Unusual Cyclopeptide Alkaloids with Antiviral Activity against Influenza A Virus from Melicope pteleifolia

Abstract: In the search for antiviral cyclopeptides against influenza A virus, five unprecedented Caryophyllaceae-type cyclopeptides (1–5) were isolated from the leaves of Melicope pteleifolia. Their chemical structures and absolute configurations were unambiguously determined by means of advanced Marfey’s analysis and comprehensive spectroscopic analyses including two-dimensional nuclear magnetic resonance and MS/MS fragmentation. Interestingly, compounds 3–5 contain an unusual heterocycle, a 3a-hydroxypyrroloindole mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Natural products provide various chemical structures for the development of drug discovery. Among them, natural resource cyclic peptides belong to a particular class of compounds that display broad activities ranging from antiviral to antibacterial and anticancer applications [2–7]. Compared with linear peptides, cyclopeptides are more stable because of the absence of both free amino and carboxyl groups in their structures.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products provide various chemical structures for the development of drug discovery. Among them, natural resource cyclic peptides belong to a particular class of compounds that display broad activities ranging from antiviral to antibacterial and anticancer applications [2–7]. Compared with linear peptides, cyclopeptides are more stable because of the absence of both free amino and carboxyl groups in their structures.…”
Section: Introductionmentioning
confidence: 99%
“…2 Very recently, the Oh group, one of our research collaborators, isolated new cyclopeptides melicoptelines A−E from the leaves of Melicope pteleifolia, which has been traditionally used in China and Vietnam for the treatment of cold and flu accompanying high fever and pain. 3 They evaluated the anti-influenza activity of the isolated melicoptelines and found that the activity of melicoptelines C−E containing a hexahydropyrrolo[2, 3-b]indole (HPI) moiety is stronger than those of other isolated melicoptelines (Figure 1). We assumed that this HPI moiety can act as an important pharmacophore and thus designed a total synthesis of melicoptelines C−E for medicinal studies of anti-influenza drugs.…”
mentioning
confidence: 99%
“…The structures of synthetic melicoptelines C−E were confirmed by spectral analysis, and these compounds were found to be identical to the natural compounds (page S-30 of the Supporting Information). 3 Furthermore, diastereomeric melicopteline 4 was also synthesized through the same procedure by applying anti-cis HPI 9b instead of syn-cis HPI 9a (Scheme 5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Melicopteline C 5 , from leaves of Melicope pteleifolia , is a cyclic hexapeptide with an unusual pyrroloindole ring system and shows potent antiviral activity. 5 A pathway for the formation of the pyrroloindole ring system from a tryptophan residue has been proposed.…”
mentioning
confidence: 99%